Effect of periodontal therapy on endothelial function and serum biomarkers in patients with periodontitis and established cardiovascular disease: a pilot study - Ana Molina; Nagore Ambrosio; María Molina; Eduardo Montero; Leire Virto; David Herrera; Elena Figuero; Mariano Sanz (Frontiers in Oral Health)
AimTo investigate the effect of periodontal therapy on endothelial function of subjects with periodontitis in stages III or IV and established cardiovascular disease.Materials and methodsA triple-blinded, parallel groups, randomized clinical trial of 6 months duration, on patients with history of coronary heart disease and periodontitis in stages III or IV was performed. Intervention consisted of steps 1 (oral hygiene instructions and professional mechanical plaque removal) and 2 (subgingival instrumentation) of periodontal therapy, including an antiseptic mouth rinse for 7 days. Patients in the control group received only step 1, with the adjunctive use of a fluoride-containing mouth rinse. Endothelial function (flow-mediated dilation [FMD]) and carotid intima-media thickness (cIMT) at baseline, 3 and 6 months, and serum markers of inflammation and cell adhesion at 3 days, 10 days, 3 and 6 months after therapy, were evaluated. Demographic characteristics, cardiovascular risk factors, history of cardiovascular diseases, medication intake, lipids profile, blood pressure, and periodontal outcomes were also evaluated. Student T, Mann–Whitney U, Chi-square and Fisher-exact tests were performed along with repeated measures ANOVA with post hoc Bonferroni's corrections.ResultsThirty-five patients were included. In the test group, improvements in pocket depth, bleeding on probing and suppuration at 6 months were significantly better than in control patients. Reductions in mean FMD [test group −3.43%; 95% confidence interval—CI [−2.68; 9.54], p = 0.487; control group −6.75%; 95% CI [1.29; 12.22], p = 0.012] and cIMT (test group −0.05 mm; 95% CI [0.01; 0.10], p = 0.014; control group −0.01 mm; 95% CI [−0.03; 0.05], p = 1.000) were observed in both groups from baseline to 6 months, without significant intergroup differences at any time-point. Differences between groups in serum inflammatory markers were detected at baseline and 3 days for interleukin (IL)-18, and at 10 days for IL-8.ConclusionPreliminary results from the present pilot study showed that steps 1 and 2 of periodontal treatment in subjects with periodontitis in stages III–IV and established cardiovascular disease induced improvements in cIMT and periodontal outcomes, although changes in FMD were not observed. Clinical Trial Registrationclinicaltrials.gov, Identifier, database (NCT02716259).